2008
DOI: 10.1007/s00467-008-0860-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravenous pulse cyclophosphamide treatment versus combination of intravenous dexamethasone and oral cyclophosphamide treatment in steroid-resistant nephrotic syndrome

Abstract: We compared, in a randomized controlled trial, the efficacy of a regimen based on intravenous (i.v.) cyclophosphamide therapy with a combination of i.v. dexamethasone and oral cyclophosphamide therapy in inducing remission in patients with steroid-resistant nephrotic syndrome (SRNS). During April 2001 to December 2003, 52 consecutive patients with idiopathic SRNS, normal renal function and renal histology findings showing minimal change disease, focal segmental glomerulosclerosis or mesangioproliferative glome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 22 publications
(38 reference statements)
1
24
2
Order By: Relevance
“…3). Treatment regimens for patients with SRNS that include oral cyclophosphamide have been tentatively advocated by the authors of a number of reports (including patients with FSGS) [16,21]; however, the results of our study suggest that the treatment regimen of oral cyclophosphamide can not be recommended-at least not to patients with SRNS with the FSGS histopathological pattern. Our institution has not adopted regimens with intravenous cyclophosphamide for the treatment of children with SRNS, but the results of other studies evaluating the efficacy of such therapeutic regimens are conflicting [12,22,23].…”
Section: Discussioncontrasting
confidence: 48%
“…3). Treatment regimens for patients with SRNS that include oral cyclophosphamide have been tentatively advocated by the authors of a number of reports (including patients with FSGS) [16,21]; however, the results of our study suggest that the treatment regimen of oral cyclophosphamide can not be recommended-at least not to patients with SRNS with the FSGS histopathological pattern. Our institution has not adopted regimens with intravenous cyclophosphamide for the treatment of children with SRNS, but the results of other studies evaluating the efficacy of such therapeutic regimens are conflicting [12,22,23].…”
Section: Discussioncontrasting
confidence: 48%
“…New trials of other immunosuppressive regimens in the treatment of SRNS have been reported [25][26][27][28][29]. Tacrolimus was an effective and well-tolerated option for SRNS patients suffering therapy resistance, dependence or intolerable side effects from other drugs [25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Children; data modified to conform to this tabulationMean age of presentation was 9.2 year which meant SRNS is common in higher age group. The mean age at onset of the SRNS in this and other studies Appeared to be a function of the glomerular morphologic lesion as children with MCD-associated SRNS tend to be younger (2.2-5.1 years)4 12,23,24,25 than those with non-MCD-associated SRNS who are older (6.2-8.72 years) [26][27][28][29] . Hypertension and hematuria are common features of non-MCD.…”
Section: Ivdiscussionmentioning
confidence: 82%
“…With the above mentioned treatment 21 (65.63%) achieved response which was similar to many other studies as different author found different levels of remission ranging from 14.8-80% depending upon various protocol 11 . Mantan et al 23 and Harri et al 32 respectively achieved 47.8% and 35.1% remission rate using i.v. dexamethasone and oral cyclophosphamide and prednisolone.…”
Section: Ivdiscussionmentioning
confidence: 96%